A atua????o do Poder Judici??rio como garantidor de aplicabilidade do princ??pio da capacidade contributiva - Farias, Ricardo Bispo (2016)
The present work demonstrates, initially, brief cuts on the constitutional paradigms of the State, from which reflections on taxation in the Liberal State, the Social State and the Democratic State of Law, as well as the movements that led to the ruptures between these paradigms. It also addresses the fundamental rights and duties recognized by the State's evolution, their main characteristics and the possible limitation of fundamental rights based on fundamental duties, in particular the fundamental duty of paying taxes. From this context, the study of the principle of contributory capacity begins, from its historical development to the positivation in the Federal Constitution of 1988. Also on the contributory capacity, the discussions are presented that involve the conceptual construction, the aspects related to the meanings and applicability of this principle, especially in its subjective sense. Once this basis is exceeded, the characteristics of the Judiciary's activity in Brazil are exposed, including the debate on "judicial activism". Finally, we present, specifically, the discussions of the Judiciary's action regarding the principle of subjective contributory capacity, as well as the possibility of using the "thesis of the limit of the limits of fundamental rights" as an argumentative effort of applicability of the subjective meaning of the principle of contributory capacity.